Mechanical Properties of a Typical Jurassic Shaximiao Sandstone Under Subzero and Deep in situ Temperature Conditions - He, R.; He, L.; Guan, B.; Yuan, C. M.; Xie, J.; Ren, L. (Frontiers in Earth Science, 2021)
Insight into the difference between the mechanical properties of rocks at low and in situ deep reservoir temperatures is vital for achieving a better understanding of fracking technologies with supercritical CO2 and liquid nitrogen. To address this issue, the fracking-related mechanical properties of the Shaximiao Formation sandstone (SS) were investigated through direct tension, uniaxial compression, and three-point bending fracture tests at a typical low temperature (Tlow) of −10°C and a reservoir temperature (Tin situ) of 70°C. The results showed that the tensile strength σt, compressive strength σc, and fracture toughness KIC of the SS were all higher at Tlow than at Tin situ, although to different extents. The KIC of the SS increased slightly more than σt at the lower temperature, while both σt and KIC of the SS increased significantly more than σc at the lower temperature. In addition to the strength, the stiffness (particularly the tensile stiffness) and the brittleness indices of SS were similarly higher at Tlow than at Tin situ. In situ monitoring using the digital image correlation technique revealed that a highly strained band (HSB) always appeared at the crack front. However, because of the inhomogeneous microstructure of the SS, the HSB did not always develop along the line connecting the notch tip to the loading point. This was a possible cause of the highly dispersed KIC values of the SS. The HSB at the crack front was notably narrower at Tlow than at Tin situ, suggesting that low temperatures suppress the plastic deformation of rocks and are therefore beneficial to reservoir stimulation.